2022
DOI: 10.1021/acsomega.2c06258
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation of Curcuma longa Root Extract and Evaluation of Its Dissolution Potential

Abstract: Medicinal plants have been widely used for therapeutic purposes for a long time, but they have been found to have some major issues such as low water solubility and bioavailability. In the present study, the nanoformulation of Curcuma longa L. plant extract was prepared to enhance its dissolution potential and biological activities. For the formulation of the nanosuspension, an ethanolic extract of C. longa was prepared through Soxhlet extraction using the nanoformulation technique. The nanosuspensions were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Both samples demonstrated a high degree of rapid release within 30 min, about 75% for ironwort and about 85% for SZ phyto-nanocarrier, reaching a maximum of 96.37% for ironwort and 99.76% for SZ phyto-nanocarrier at 60 min (Figure 12A,C). These results are in good agreement with the requirements imposed by international regulations [117].…”
Section: In Vitro Dissolution Assaysupporting
confidence: 91%
See 3 more Smart Citations
“…Both samples demonstrated a high degree of rapid release within 30 min, about 75% for ironwort and about 85% for SZ phyto-nanocarrier, reaching a maximum of 96.37% for ironwort and 99.76% for SZ phyto-nanocarrier at 60 min (Figure 12A,C). These results are in good agreement with the requirements imposed by international regulations [117].…”
Section: In Vitro Dissolution Assaysupporting
confidence: 91%
“…Recent literature results have reported that the bioavailability of a drug depends on various physical characteristics of drug delivery, such as particle size, shape, and long-range structural (atomic-scale) order [117,118]. The results indicate that both samples had increased dissolution time in an acidic environment (pH 4) over time.…”
Section: In Vitro Dissolution Assaymentioning
confidence: 97%
See 2 more Smart Citations
“…10 The biosynthetic scope was also extended to include biosynthesis, solvent-free synthesis, microwave-assisted synthesis, and ultrasound-assisted synthesis. 11,12 The eld of biosynthesis is rapidly growing, with many innovative new methods being developed. 13 With its many advantages over traditional methods, biosynthesis is likely to become the standard for synthesizing nanomaterials in the future.…”
Section: Introductionmentioning
confidence: 99%